A Boy's Short Life; The story of Warren Braedon/ Louis Johnson - Haebich, Anna; Mickler, Stephen (UWA Publishing, 2013)
He never knew his name, he never knew his mother, he never knew his family, he never knew his people, he never knew his country. Born Alice Springs, 4th January, 1973, murdered Perth, 4th January, 1992 … because he was black. Louis St John Johnson, born Warren Braedon into a Luritja and Arrernte family, was taken from his mother in Alice Springs at just three months old. Despite growing up with the love and care of his adoptive family, Louis was increasingly targeted by school bullies and police for his Aboriginality, and his attempts to find his natural family in Alice Springs were thwarted by bureaucracy. Walking home on his nineteenth birthday, Louis was brutally murdered by a group of white youths ‘because he was black’. This story captures the dark heart of racism in modern Australia, and the history, government policies and community attitudes that marked this boy out for a short life.